Penggunaan FMEA Dalam Mengindentifikasi Resiko Kegagalan Pada Proses Produksi Cetak Blok Kalender (Studi Kasus : PT. XYZ) - Rachmah Nanda Kartika; Nafiah Ariq Hidayah; Muadzah (CV. Multi Kreasi Media, 2022)
PT. XYZ is one of the printing companies in Jakarta. The company produces graphic products such as smart cards, the Qur'an, packaging, calendars, books, and security documents. The manufacturing production process always strives for no defective products. To minimize production failures that will occur, a system that supervises product quality is needed, called a quality control system. Printing problems that occur in PT. XYZ on the four-vel calendar product has 4 types of defects namely misregister, striped color, set-off, and dot gain. The product data for calendar block printing products in 2022 is 6500 pcs. The number of defects is high. So that the problem needs to be immediately corrected and analyzed accurately. The method used in this study was FMEA. This method identifies problems that occur in the field by identifying production factors and determining the severity of the problem through the Risk Priority Number (RPN) value. The higher the RPN value, the bigger the problem. If the bigger the problem, then the risk of the problem must be prioritized to be overcome. Based on the percentage of each type of printing defect that occurs in PT. XYZ has the most product defects is the striped color on the vel 4 block mold. The identification results based on the three highest RPN values are caused by low-speed engines and often die, the rollers are old and do not have a densitometer measuring instrument. The main risk control measures that the company can take, namely overhaul, buying measuring instruments to replace the rollers. Then after repairs a check sheet is required.